GERAKAN PEMANFAATAN LAHAN SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT UNTUK KETAHANAN PANGAN PADA MASA PANDEMI COVID-19 DI KOTA YOGYAKARTA - Utomo, Lantip Fajar; Effendi, David (Caraka Prabu : Jurnal Ilmu Pemerintahan, 2022)
This research aims to discuss how the strategy of community empowerment in building food self-sufficiency in the City of Yogyakarta Covid-19. Qualitative research using an explanatory method. Data collection techniques were carried out through observation, interviews, and documentation. Based on the research that has been done that the land use movement and the existence of community empowerment programs during the Covid-19 pandemic in the city of Yogyakarta. The land use movement functions as an effort to build food self-sufficiency and community-based local community empowerment. This program is also a space for collaboration between community stakeholders and the agriculture office as well as financial support from the special budget of the Special Region of Yogyakarta. Other findings, there are several benefits for farmer groups and the surrounding community, namely being able to create and develop group potential, employment opportunities, helping group welfare, being able to meet community food needs. In addition, there are obstacles experienced such as erratic weather conditions affecting crop yields, lack of participation among group members, lack of consistency to maintain every agenda that will be carried out and market support to buy community products.